2018
DOI: 10.1097/md.0000000000012945
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of bioelectrical impedance analysis for detecting breast cancer-related lymphedema

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 21 publications
1
29
1
Order By: Relevance
“…In this respect, bioimpedance spectroscopy would have been valuable in terms of measuring the extracellular fluid directly. 31 Previous studies indicate an overall trend in favor of PRT, as illustrated by the most recent meta-analysis, in which pooled data from 5 PRT trials during or after adjuvant treatment in women with or at risk for lymphedema indicated a significantly lower risk of incidence/exacerbation (odds ratio, 0.53; confidence interval, 0.31-0.90). 8 When the 2 trials from this meta-analysis that tested PRT during adjuvant treatment in women at risk for lymphedema were isolated, 15,16 no protective effect was found with no statistically significant difference between groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this respect, bioimpedance spectroscopy would have been valuable in terms of measuring the extracellular fluid directly. 31 Previous studies indicate an overall trend in favor of PRT, as illustrated by the most recent meta-analysis, in which pooled data from 5 PRT trials during or after adjuvant treatment in women with or at risk for lymphedema indicated a significantly lower risk of incidence/exacerbation (odds ratio, 0.53; confidence interval, 0.31-0.90). 8 When the 2 trials from this meta-analysis that tested PRT during adjuvant treatment in women at risk for lymphedema were isolated, 15,16 no protective effect was found with no statistically significant difference between groups.…”
Section: Discussionmentioning
confidence: 97%
“…Although water displacement is considered a valid measurement of arm volume, it cannot distinguish between swelling and other tissue changes. In this respect, bioimpedance spectroscopy would have been valuable in terms of measuring the extracellular fluid directly …”
Section: Discussionmentioning
confidence: 99%
“…BIA also is a non-invasive measure and is convenient for both the physician and the patients. Reference values for healthy populations and standards for diagnosis of lymphedema have been established for BIA (33). However, considering individual variability especially noted for obese individuals (34), the patient's longitudinal value after CDT can be used as a reference during longterm maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Bioelectrical impedance technology is a simple, safe, and noninvasive method to measure lymphedema. It obtains the electrical impedance of each segment of the body by measuring the frequency current acting on the segments and analyzing the tissue composition [ 5 , 6 ]. When the current frequency is low, the current is mainly being transmitted through extracellular fluid, which allows the measurement of extracellular water (ECW); when the current frequency is high, the current is being transmitted through intracellular and extracellular fluid, which allows the measurement of total body water (TBW) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%